Pengaruh Struktur Modal, Pertumbuhan Perusahaan, Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2015-2019 - Olivia Fajariani; Kersna Minan; Desi Ika (Cattleya Darmaya Fortuna, 2022)
Increasing the value of the company is a long-term goal that should be achieved by the company which will be reflected in the market price of its shares because investors' assessment of the company can be observed through the movement of the company's stock price that is traded on the stock exchange. This study aims to determine the effect of capital structure, firm growth, and profitability on firm value with dividend policy. This study aims to determine the effect of capital structure, firm growth and profitability on firm value through dividend policy. The research sample is 32 manufacturing companies listed on the Indonesia Stock Exchange with observations from 2015 to 2019. The research method uses path analysis. Based on the results of the study indicate that the company's growth and profitability have a significant effect on dividend policy, while capital structure has no effect on dividend policy. Profitability has a significant effect on firm value, while capital structure, firm growth and dividend policy have no effect on firm value. Dividend policy cannot mediate the effect of capital structure, company growth and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.